Clinical performance of the Solana® Point-of-Care Trichomonas Assay from clinician-collected vaginal swabs and urine specimens from symptomatic and asymptomatic women. (4th March 2017) - Gaydos, CA; Schwebke, J; Dombrowski, J; Marrazzo, J; Coleman, J; Silver, B; Barnes, M; Crane, L; Fine, P
ABSTRACT: Background: Solana® (Quidel) is a new rapid (<40 min.) point-of-care (POC) test for qualitative detection of Trichomonas vaginalis (TV) DNA. The assay has two steps: 1) specimen preparation, and 2) amplification and detection using isothermal Helicase-Dependent Amplification (HDA). The objective was to demonstrate the performance of Solana for vaginal swabs and female urines based on comparison to wet mount and TV culture. Performance was also compared to the Aptima-TV assay. Methods: Urine and four clinician-collected vaginal swabs were collected. The first two were used for FDA composite reference (wet mount; InPouch TV Culture). The third swab was used for Solana. Sensitivity/specificity were based on the reference method. A specimen was considered positive if either test was positive. The fourth swab was for Aptima-TV. Results: Vaginal swabs and urines were obtained from 501 asymptomatic and 543 symptomatic women. Prevalence of TV by was 11.5%. For swabs, Solana® demonstrated high sensitivity and specificity from asymptomatic (100%/98.9%) and symptomatic (98.6%/98.5%) women, as well as for urines from asymptomatic (98.0%/98.4%) and symptomatic (92.9%/97.9%) women, compared to the reference method. Compared to Aptima-TV, the sensitivity/specificity was 89.7%/99.0% for swabs and 100%/98.9% for urines. Conclusion: The Solana® assay performed well compared to the reference assays.